OpuntiaGenesis: The hybrid generating plant - Aquadro, Gabriellle (School of Architecture, Planning and Geomatics, 2014)
This design dissertation explores the possibility of creating a piece of architecture from a singular biological parameter (the Opuntia ficus-indica/Prickly pear), that is both the fuel and the generator of the architectural programme, materiality, spatiality and structure. The main intention of this architectural investigation is to explore a range of alternative processes, strategies and facilities that can be used to uplift the community of Sutherland as well as the greater Hoogland municipality. The key programmatic feature is a result of the viable and celebrated capacity of the Opuntia species to be used as the main digester feed during anaerobic decomposition (biogas generation). This characteristic of the Opuntia species has informed the development of a sustainable closed-loop programmatic system that consist of the production of biogas as well as the generation of all the Opuntia by-products, including; medicinal, food, liqueur and alternative building materials. Whilst the programme is driven by the physical attributes of the Opuntia species, the architectural interrogation is a result of a series of biomimetic, parametric and materialecological investigations of both the Opuntia species as well as the site at a macro and micro scale. With this in mind the product of such a system hopes to become an Energy Lab that is not only based on the production of energy, but a lab that’s very layout, fabric and structure is fuelled by the animation and optimisation of Opuntia matter. Moreover it is essential to recognise that Opuntia matter is a product of ambient energy, making the treatment of light the essential tool in the development of this architectural design dissertation.